Evaluation of Buprenorphine LUCIO Immunoassay versus GC-MS Using Urines from a Workplace Drug Testing Program - Alves, Marcela Nogueira Rabelo; Piccinotti, Alberto; Tameni, Silvia; Polettini, Aldo (Journal of analytical toxicology, 2013)
The buprenorphine (BUP) LUCIO Nal Von Minden screening assay was evaluated. Urine samples from subjects enrolled in a workplace drug testing program were screened according to the manufacturer's instruction using a Roche COBAS Integra 800 analyser. For gas chromatography-mass spectrometry (GC-MS) confirmatory analysis, samples were submitted to enzymatic hydrolysis with β-glucuronidase and mixed-mode solid-phase extraction. Imprecision (coefficient of variation) for 3.0, 7.0, and 13.0 ng/mL calibrators varied within 2.8-8.7 intra-day (n = 20) and 7.7-8.6 inter-day (n = 19). Inaccuracy (bias) was between -5.6-30.5 intra-day and -13.2-4.2 inter-day. At the 5 ng/mL cut-off, the immunoassay showed 100% sensitivity and 88% specificity, with an overall agreement of 94% between immunoassay and GC-MS. Raising the cut-off to 10 ng/mL provided an identical overall agreement between immunoassay and GC-MS (94%), despite the decrease in sensitivity (90%) and the increase in specificity (100%). According to these results, the BUP LUCIO Nal Von Minden screening assay provides adequate sensitivity and specificity for BUP screening in urine samples using a cut-off concentration of 5 ng/mL.